The system of crop intensification: Agroecological innovations for improving agricultural production, food security, and resilience to climate change - Abraham, Binju; Adeoluwa, O.O.; Araya, Hailu; Berhe, Tareke; Bhatt, Yogesh; Edwards, Sue; Gujja, Biksham; Khadka, Ram Bahadur; Koma, Y.S.; Sen, Debashish; Sharif, Asif; Styger, Erika; et al. (Technical Centre for Agricultural and Rural Cooperation, 2014)
There is growing consensus that to meet global food-security requirements, agricultural sectors will need to pursue appropriate strategies for sustainable intensification of production. This volume reports on current ‘work in progress’ to achieve this via an approach known as System of Crop Intensification (SCI). Collated from the contributors’ work with farmers in their respective countries – and illustrated throughout with case studies, data, pictures and feedback – it presents a set of ideas and experiences to encourage people to think ‘outside the box’ of current practices.